Implementasi Program Redistribusi Tanah di Kantor Pertanahan Kabupaten Minahasa Tenggara Tahun 2021 - Hidayat Andhi Dhinata; Shirley Y V I Goni; Femmy C M Tasik (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this study is to analyze the Implementation of land redistribution program in the Kantor Pertanahan Kabupaten Minahasa Tenggara in 2021. Research uses descriptive methods with qualitative approaches. The study was conducted in Southeast Minahasa Regency using empirical data obtained through observations and interviews. The focus of this research is based on Edward III's theory with four aspects, namely communication, resources, disposition, and bureaucratic structure. The results showed that the Implementation of land redistribution program in the Kantor Pertanahan Kabupaten Minahasa Tenggara in 2021 was carried out based on the Undang-Undang No. 5 Tahun 1960 based on social justice for the entire community. Aspects of communication in the delivery of land redistribution programs implemented with extensions do not run optimally. It is also affected by limited human resources, it is the measurement and inventory officer. Furthermore, in the aspect of bureaucratic structure there is a problem of the person in charge of activities that differ between physical work and budget, and the absence of Standard Operating Procedures (SOPs) in this land redistribution activity. In the aspect of communication through counseling during the Covid-19 Pandemic it is recommended that it be implemented gradually with certain methods, schedules, and quotas. Kantor Pertanahan Kabupaten Minahasa Tenggara is advised to increase the number of employees to support the implementation of land redistribution activities both civil servants and non-civil servants. Furthermore, in the aspect of bureaucratic structure, physical and budgetary work responsibilities must be in the same institution and must be made standard operating procedure (SOP) to be a guideline that facilitates the implementation of such activities